A model for computing vibration induced stresses of electronic components in a general flexible mounting - Silva, Gustavo H.C.; Paupitz Gonçalves, Paulo J. [UNESP] (Elsevier, 2013)
This paper develops a novel full analytic model for vibration analysis of solid-state electronic components. The model is just as accurate as finite element models and numerically light enough to permit for quick design trade-offs and statistical analysis. The paper shows the development of the model, comparison to finite elements and an application to a common engineering problem. A gull-wing flat pack component was selected as the benchmark test case, although the presented methodology is applicable to a wide range of component packages. Results showed very good agreement between the presented method and finite elements and demonstrated the usefulness of the method in how to use standard test data for a general application. © 2013 Elsevier Ltd.
Keywords: Analytic models; Benchmark tests; Component packages; Design tradeoff; Electronic component; Engineering problems; General applications; Solid state electronics; Benchmarking; Vibration analysis